Contrastive analysis of associative mechanisms of "human body build" concept verbalization: In English, Russian and Armenian adjectives - Matevosyan, Kristina (Bulletin of Yerevan University H: Russian Philology, 2022)
The objective of the study is to identify similarities and differences in the associations and methods of nomination, by extracting and analyzing the semantic components in adjectives describing physical characteristics of the human body in English, Russian and Armenian. The semantic analysis of the studied lexicosemantic group revealed that the associative mechanisms involved in the description of physical characteristic of the human body are based on the national cultural tradition. Comparison with animals and plants is used in a number of adjectives, however, different in the three languages studied. The allocation of certain parts of the body, yet not always the same in English, Russian and Armenian, is also observed. Thus, thinness is associated with sickness, while short stature in English and Armenian is identified as something incomplete.Adjectives derived from the names of literary characters and famous people are considered separately.Thus, the study revealed certain unity of associative images based on universal human cultural experience, as well as a number of diversities, conditioned by geographical location, landscape, national features, customs and other factors that contribute to a language peculiarity in the consciousness of the English, Russian and Armenian language speakers.
Keywords: adjectives; physical characteristics of human body; verbalization; linguistic picture of the world